Characterization Of Hemicellulose-Carboxymethyl Cellulose Blend Biofilm Fabricated From Oil Palm Trunk - Ridzuan, Farah Fazlina Mohd (2024)
The use of synthetic polymers is not essential due to environmental issues. Hence, the green materials have been extracted from biomass waste to produce a biopolymer in order to replace the synthetic polymer. Oil palm trunk (opt) is a solid waste that is abundantly available throughout the year. Due to this concern, hemicellulose film (hc) and carboxymethyl cellulose (cmc) were successfully prepared from oil palm trunk (opt) in this research study. Hc and cmc were blended by the solution casting method to produce blend biofilm at 0%, 20%, 40%, 60%, and 80 % hc and cmc loading. The cmc used was compared between commercial cmc (cmc-c) and the extracted opt cmc (cmc-t). The raw material and biofilm sample were characterized by chemical composition, fourier transmission infrared spectroscopy (ftir), energy-dispersive x-ray spectroscopy (sem-edx), x-ray diffraction (xrd), thickness, visual transparency, contact angle, solubility, moisture content, tensile strength, scanning electron microscopy (sem), differential scanning calorimetry (dsc), thermogravimetric analysis (tga) and biodegradability analysis. According to the results, chemical composition showed that the vascular bundle had more cellulose while the parenchyma had more hc. Moreover, the ftir of parenchyma and vascular bundle were successfully identified. Then, the sem-edx and xrd revealed the element in cmc, and the crystallinity of cellulose reduced when the chemical structure was interrupted by the addition of carboxymethyl group. Then, the result of hc-cmc blend biofilm revealed that the thickness increased while the visual transparency contact angle decreased.